EVALUATION OF DIFENOCONAZOLE 3% WS AS SEED TREATMENT AGAINST KARNAL BUNT IN WHEAT BIJENDER KUMA - BIJENDER KUMAR (The Bioscan, 2019)
The present study was undertaken to evaluate the efficacy of difenoconazole 3% WS against Karnal bunt along with some recommended fungicide. Based on the data of two crop seasons it can be concluded that the spraying of propiconazole 25% EC @ 500ml/ha at anthesis was most effective fungicide both in terms of managing the Karnal bunt of wheat and improving the yield. Among the seed treatments, seed treatment with thiram @ 3.00g/ kg seed was found most effective in improving the field emergence. However, the test fungicide difenoconazole 3% WS had no beneficial effects on field emergence, disease management and yield as compare to check. Nevertheless, the test fungicide difenoconazole 3% WS had no phytotoxic effects on wheat plants during both the crop seasons even at the highest dose tested.